MODELING OF PASSENGER FLOW AT CITY RAILWAY TRANSPORT STATIONS - Lutsyk, O.; Stepanchuk, O.; Yanovsky, P. (Science-based technologies, 2014)
In this article, model of passenger flow distribution in regard to their waiting time at city railway transport stations is constructed. For modelling, developed method is used, in which is fill that the distribution of passengers in regard to waiting time is consistent with function of Erlang distribution of k order. Taken as a basis the results of experiment that was carried out on the existing network of city railway transport in Kiev. The matching of the empirical distribution with the theoretical is carried out, to obtain validity check of practical results and appropriateness of using the considered method. We determined the value of waiting time for most users of this type of public transport with the help of accumulative graphic the passenger flow distribution.